Production networks in local labour market areas - Giovanni Barbieri; Cinzia Conti (European Regional Science Association (ERSA), 2010)
The aim of the paper is to describe the structure, the dimension and the features of the net designed on the territory by the relationships between the headquarters and the local units of multi-location enterprises in Italy. Network analysis has been applied to spot these relationships, considering, as nodes, the different territorial locations (at the labour local market areas detail) of the headquarters and of the local units and, as ties, the number of workers in local units employed by the multi-location enterprise. In this way, each tie reveals the existence (and the intensity) of a productive relationship between two different territories. The results of the study clearly show that in Italy the system of multi-location enterprises is shaped as a "small world" (Milgram, 1967; Watts and Strogatz, 1998), and also as a scale-free network with a limited number of hubs (Barabási e Albert 1999). The analysis underlines that the interactions among enterprises and among territories is a key factor for development and innovation. On the other hand, hubs make the network vulnerable to non-random shocks.
Keywords: 330